Endoscopic Findings of Upper Gastrointestinal Lesions in Patients with Pancreatic Cancer - Ohtsubo, Koushiro; Watanabe, Hiroyuki; Mouri, Hisatsugu; Yamashita, Kaname; Yasumoto, Kazuo; Yano, Seiji (JOP. Journal of the Pancreas, 2012)
Context Pancreatic cancer is often complicated with upper gastrointestinal lesions. However, there have been few endoscopic studies in pancreatic cancer patients. We retrospectively investigated the upper gastrointestinal lesions in patients with pancreatic cancer who underwent upper gastrointestinal endoscopy. Methods Upper gastrointestinal endoscopy was performed in 75 patients with pancreatic cancer between 2003 and 2010. We examined upper gastrointestinal lesions, such as gastroduodenal invasion, ulcers, esophagogastric varices, radiation-induced gastroduodenal mucosal lesions, and portal hypertensive gastropathy. Results Among the 53 patients with pancreatic cancer who underwent upper gastrointestinal endoscopy at diagnosis, 23 gastrointestinal lesions were observed in 20 patients (38%) as follows: gastroduodenal invasion (n=11), esophagogastric varices (n=7), gastroduodenal ulcers (n=3), portal hypertensive gastropathy (n=1) and duodenal metastasis (n=1). Among the 75 patients with pancreatic cancer, 56 gastrointestinal lesions were identified in 46 patients (61%) during the clinical course as follows: gastroduodenal invasion (n=20), esophagogastric varices (n=14), radiation-induced gastroduodenal mucosal lesions (n=9), gastroduodenal ulcers (except radiation-induced ulcers) (n=8), portal hypertensive gastropathy (n=3), duodenal metastasis (n=1), and gastrointestinal bleeding from unknown primary site (n=1). Twenty-nine (52%) of the 56 gastrointestinal lesions showed symptoms related to the lesions. Fifteen (27%) lesions were accompanied by upper gastrointestinal bleeding. Fourteen (25%) lesions developed according to the progression of pancreatic cancer. Conclusion We should pay attention to upper gastrointestinal lesions in patients with pancreatic cancer. Image: Case of pancreatic head cancer with duodenal invasion.